Assessment of lifetime exposure to trihalomethanes through different routes. Issue 4 (23rd March 2006) - Villanueva, C M; Cantor, K P; Grimalt, J O; Castaño-Vinyals, G; Malats, N; Silverman, D; Tardon, A; Garcia-Closas, R; Serra, C; Carrato, A; Rothman, N; Real, F X; et al.
Abstract : Objectives: To evaluate lifetime exposure to trihalomethanes (THM) through ingestion, inhalation, and dermal absorption in a hospital based case-control study of bladder cancer conducted between 1998 and 2001 in five areas of Spain. The study base was comprised of subjects living in the catchment areas of the participating hospitals. Methods: Individual information on water related habits was obtained from personal interviews of 1219 cases and 1271 controls: residential and occupational history, drinking water source at each residence and job, amount of water consumption, frequency and duration of showering, bathing, and swimming pool attendance. THM levels, water source history, and year when chlorination started in study areas were ascertained through measurements in drinking water samples and questionnaires to water companies and local authorities. Estimates of THM levels covered 79% of the subjects' person-years of exposure. Results: Current and historical average THM levels in water were correlated. Control subjects reported that drinking water source in the last residence was municipal for 63%, bottled for 22%, private well for 2%, and other sources for 13%. For the time window between age 15 and the time of interview, average residential THM level was 32.2 μg/l. THM exposure through ingestion was 23.7 μg/day on average, and was correlated with the ingestion THM level in the workplace. Overall, 79% usually took showers, 16% usually took baths, and 13% had ever attended a swimming pool. Between 21% and 45% of controls unexposed to THM through ingestion were evaluated as moderately or highly exposed through showering or bathing, and 5–10% were exposed through swimming in pools. Conclusion: The importance of evaluating different routes is underscored by findings from experimental studies showing substantial differences in THM uptake and internal distribution by route.